Effect of folic acid supplementation on nerve conduction velocity in diabetic polyneuropathy patients. (3rd April 2019) - Mottaghi, Tayebeh; Khorvash, Fariborz; Maracy, Mohammadreza; Bellissimo, Nick; Askari, Gholamreza
ABSTRACT: Objectives : In diabetic polyneuropathy (DPN) patients, the effect of folic acid and homocysteine has been related to components of nerve conduction velocity (NCV). The objective of this study was to determine the effect of folic acid supplementation on NCV in DPN patients. Methods : Patients were randomized to receive either 1 mg of folic acid (n = 40) or placebo (n = 40) for 16 weeks. Blood samples were collected to assess serum folic acid and homocysteine concentrations, and NCV was performed for assessment of diabetic neuropathy. Results : At 16 weeks, in the supplemented group, serum levels of folic acid (p < 0.001) increased, homocysteine concentrations decreased (p < 0.001), with no change in serum vitamin B12 levels. There was a significant increase in sensory sural amplitude (p < 0.001), and components of motor nerves, including amplitude (p = 0.001) and velocity (p < 0.001), but decreased onset latency of peroneal (p = 0.019) and tibial (p = 0.011) motor nerves. Conclusion : Our data suggest that supplementation with 1 mg of folic acid for 16 weeks may be useful for enhancing NCV in DPN patients.